Carnal innocence - Roberts, Nora (Piatkus, 2020)
In the small town of Innocence, Mississippi, days are long, nights are fragrant, and secrets are hard to keep. But when a brutal killer starts claiming the lives of the town's most attractive women, lifelong neighbors are forced to wonder if the culprit is a stranger lurking in the bayou ... or someone right next door.